The Cancellation of Grants in The Perspective of Civil Law and Islamic Law - Mahasin, Zahra Zara (Universitas Negeri Semarang, 2022)
From birth, there is no human being in this world who can live alone without another human being. This is because humans are social beings. In life with human beings must be mutual helping. Forms help please this is diverse that there is a form of Services, Sale, Buy, Gift and so forth and one form of help please that there is a form of Grant. Indeed, all humans will die. This event will lead to inheritance in a civil law. Usually heirs while still alive give grants or donations either to his heirs or to others. And usually the grant is not known by the heirs, which then raises the issue of the heritage property. Thus came the issues and also the questions about how the civil law regulates the grant in the Civil Code. So in this paper will explain what grants and grant cancellation and examples of cases that occurred in Indonesia related to the problem of grants.